2006
DOI: 10.1002/jor.20173
|View full text |Cite
|
Sign up to set email alerts
|

Moderate soft tissue trauma delays new bone formation only in the early phase of fracture healing

Abstract: The aim of this study was to investigate the effect of a moderate soft tissue trauma to the course of fracture healing in a standardized animal model. Thirty‐eight Wistar rats were randomly divided into a fracture group (F, n = 19) and a group with a fracture and a soft tissue trauma (F + STT, n = 19). The fracture and the soft tissue trauma were created using an impact device with a standardized energy. All fractures were stabilized by two Kirschner wires. Three rats were measured for blood flow and sacrifice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 15 publications
2
49
2
2
Order By: Relevance
“…As the individual callus areas varied, points on the grid covering empty area outside the boundaries of a particular callus were excluded from analysis. The grid-measuring method was performed in a blinded fashion and has repeatability of better than 90% [8,9]. The number of animals achieving bony bridging of the osteotomy gap in the periosteal (medial and lateral), intracortical (medial and lateral), and endosteal zones was quantified (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…As the individual callus areas varied, points on the grid covering empty area outside the boundaries of a particular callus were excluded from analysis. The grid-measuring method was performed in a blinded fashion and has repeatability of better than 90% [8,9]. The number of animals achieving bony bridging of the osteotomy gap in the periosteal (medial and lateral), intracortical (medial and lateral), and endosteal zones was quantified (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…In the control group the periosteal callus contained more fibrous cartilage (14.1%), which is characteristic for a flexibly fixed fracture with cyclical interfragmentary movements. 17 In contrast, the TD group showed somewhat less fibrous cartilage (7.2%), comparable to values seen in callus distraction (approximately 5% 12 ). The bone formation rate (Table 3) at days 20 and 30 showed that temporary distraction, which was finished at day 19, stimulated the peripheral callus formation on days 20 and 30.…”
Section: Discussionmentioning
confidence: 55%
“…Some aspects of fracture care, such as motion at the fracture site (Sarmiento et al 1977), surgical delay (Smith et al 1974, Coutts et al 1982, type of fixation (Claes et al 2006) and periosteal stripping during open reduction (Hayda et al 1998), have been shown to affect fracture union.…”
Section: Factors Affecting Outcomementioning
confidence: 99%